The effect of boycotts on market demand in companies listed on the Indonesian stock exchange - Nurul Mumtazah Simpajo; Muchriana Muchran (IECON: International Economics and Business Conference, 2024)
This study aims to see the impact of boycotts on market demand by comparing data on stock prices and sales before and after boycotts, the market demand indicators in question are the prices and sales of shares of companies listed on the Indonesian stock exchange. In recent years, boycotts have become increasingly common, especially in countries with large Muslim populations, including Indonesia. In 2023, MUI issued several wide-ranging fatwas, one of which was fatwa number 83 of 2023 issued on November 8, 2023. This fatwa regulates the law of supporting Palestine in the context of the Palestinian-Israeli crisis. This research method uses quantitative methods by using data analysis techniques, namely paired T-test techniques. This study examines the company's stock price and sales data before and after the boycott of pro-Israel products. Stock price and sales data were taken from the official website of the Indonesia Stock Exchange (IDX) as many as 938 companies. The results of this study reveal that there is an effect of boycott action on stock prices and sales in 10 companies listed on the Indonesia Stock Exchange whose products are pro-Israel.